1989
DOI: 10.1063/1.456307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a quantum-mechanical lattice on the electronic structure and dd spectrum of the (MnF6)4− cluster in Mn2+ :KZnF3

Abstract: The electronic structure of the Mn2+ :KZnF3 impurity system has been computed by means of a Hartree–Fock–Roothaan cluster model. First, the Mn2+ center has been simulated by the (MnF6 )4− unit in vacuo. Then, the effects of the KZnF3 lattice have been included in the cluster calculation using three different lattice models. The well-known point–charge approximation has been compared with two rigorous quantum–lattice models derived from the ideas of the theory of electronic separability. In these two models the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…This procedure has to be improved in order to obtain a realistic description of the lattice distortions around the impurity. [9][10][11][12]15,18,21,24,26,27,31,33 Model potentials have been developed to represent the effects of the environment on the active cluster, that include attractive and repulsive quantum-mechanical terms aside from the classical Madelung term. 34 (b) An active cluster size that is too small.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has to be improved in order to obtain a realistic description of the lattice distortions around the impurity. [9][10][11][12]15,18,21,24,26,27,31,33 Model potentials have been developed to represent the effects of the environment on the active cluster, that include attractive and repulsive quantum-mechanical terms aside from the classical Madelung term. 34 (b) An active cluster size that is too small.…”
Section: Introductionmentioning
confidence: 99%
“…From the optical spectra of K 3 NiF 6 crystal, Allen and Warren [17] found that B ≈ 703 cm −1 (so ƒ γ ≈ 0.588), |D q | ≈ 1620 cm −1 and suggested that the ground orbital state of (NiF 6 ) 3-clusters is the low spin 2 E. This point is supported by the TanabeSugano diagram [18,19], in which for 3d 7 ions in octahedra, if |D q /B| > 2.2, the ground orbital state is the low-spin 2 E state. Since for 3d n clusters, the parameter Dq µ R 0 −n (where 3.5 6.5 n ≈ - [20,21]), and the Racah parameter B or C increases slightly with the increasing average impurity-ligand distance R 0 [22,23]. Thus, from the distances R 0 ≈ 1.90 Å and 2.02 Å for (NiF 6 ) 3− clusters in K 3 NiF 3 and RbCaF 3 crystals (note: in the pure crystals, the distance R 0 is close to the sum of ionic radii [16] C ≈ 2885 cm…”
Section: Calculationsmentioning
confidence: 98%
“…24 Along this line, it should be noticed that according to Kohn, the localization of electrons is the fingerprint of every insulating material. 25,26 Bearing in mind these considerations, it turns out that 10Dq for an octahedral MX 6 c-6a complex microscopically depends on the M-X distance, R. The law describing the R dependence of 10Dq derived from theoretical calculations is found to be [24][25][26][27][28] …”
Section: ͑1͒mentioning
confidence: 99%